2019
DOI: 10.1111/ger.12410
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in epidemiology and management of facial trauma in a Swiss geriatric population

Abstract: Objective To assess the prevalence and surgical treatment of facial fractures in a Swiss population aged 65 and over. Background The knowledge of the characteristics of geriatric trauma may help to prevent injuries and better allocate clinical resources for the management of multimorbid patients. Material and methods This study retrospectively evaluated a cohort of 181 patients who presented at the Bern University Hospital in Switzerland from May 2012 to September 2016. Data on age, gender, aetiology and type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
6
16
1
Order By: Relevance
“…Regarding gender, the literature over the past 20 years has shown a male-female relationship in which men dominate over women, especially in developing countries, 13,14,20,32 but the reverse relationship has been described in reports from Japanese, 17 Australian 25 and some European 27,29,30 centres. Similarly, the present study reported a M:F ratio slightly in favour of men, but with a clear predominance of men in Asian centres and women in Brazilian and European centres.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding gender, the literature over the past 20 years has shown a male-female relationship in which men dominate over women, especially in developing countries, 13,14,20,32 but the reverse relationship has been described in reports from Japanese, 17 Australian 25 and some European 27,29,30 centres. Similarly, the present study reported a M:F ratio slightly in favour of men, but with a clear predominance of men in Asian centres and women in Brazilian and European centres.…”
Section: Discussionmentioning
confidence: 99%
“…Falls are most often observed at the place of residence, mainly in bathrooms or toilets, from a height not exceeding 1 meter. The age of patients and height of the fall are inversely correlated [1,2,19,22]. Even low-energy falls are a more common cause of death in the elderly compared to younger people [8].…”
Section: Discussionmentioning
confidence: 99%
“…The cultural differences, the high socioeconomic standard, lifestyle, and the alpine surroundings may influence the etiology of facial trauma in Switzerland [13]. There have only been a few studies on dental and maxillofacial injuries in the Swiss population, and none on immigrants to Switzerland [13][14][15][16][17].…”
Section: Triage Systemmentioning
confidence: 99%